Analysis Service Quality Impact on Registration Section and Patient Satisfaction during Covid-19 Pandemic at General Hospital of Muhammadiyah University of Malang - Andy Oky Setiawan; Setyo Budi Susanto; Agustin Widyowati (Journal of Hospital Management and Services, 2022)
General Hospital of Muhammadiyah University of Malang is one of the largest hospitals that provides health services for people in the Malang area and its surrounding. It is also strived to improve the quality services and developed a complete infrastructure facility continuously to obtained good health services. This research used crossectional method. ode yang digunakan dalam penelitian ini adalah Crosssectional. The number of total population about 13205 with total 99 participants for sample. The sampling method using Purposive Sampling. The data collection using questionnaries and prosessed with Chi-square test.The result showed there was significant impact between service quality on registration section and patient satisfaction during Covid-19 pandemic. The value of significant impact between service quality on registration section and patient satisfaction is 0,002, which means Ho rejected and the value of correlation coefficient 0.313 which means theres is correlation between service quality on registration section and patient satisfaction during Covid-19 pandemic. There is a significant impact between between service quality on registration section and patient satisfaction.